Low-temperature sintering and microwave dielectric properties of B2O3-added ZnO-deficient Zn2GeO4 ceramics for advanced substrate application. Issue 14 (November 2018) - Ma, Xing-Hua; Kweon, Sang-Hyo; Im, Mir; Nahm, Sahn
Abstract: ZnO-deficient Zn2- x GeO4- x ceramics with 0.05 ≤ x ≤ 0.15 were synthesized because a ZnO secondary phase is formed in the stoichiometric Zn2 GeO4 ceramics synthesized using micrometer-sized ZnO and GeO2 powders. The Zn1.9 GeO3.9 ceramic sintered at 1000 °C showed a homogeneous Zn2 GeO4 phase with good microwave dielectric properties: εr of 6.8, Q × f of 49, 000 GHz, and τf of −16.7 ppm/°C. However, its sintering temperature was still too high for it to be used as an advanced substrate for low-temperature co-fired ceramic devices. Therefore, various amounts of B2 O3 were added to the Zn1.9 GeO3.9 ceramics to reduce their sintering temperature. Owing to the formation of a B2 O3 -GeO2 liquid phase, these ceramics were well sintered at low temperatures between 925 °C and 950 °C. In particular, 15 mol% B2 O3 -added Zn1.9 GeO3.9 ceramic sintered at 950 °C showed promising microwave dielectric properties for advanced substrates without the reaction with an Ag electrode: εr = 6.9, Q × f = 79, 000 GHz, and τf = −15 ppm/°C.